Bio-based photo-reversible self-healing polymer designed from lignin. Issue 24 (22nd November 2021) - Sinha Roy, Pallabi; Mention, Matthieu M.; Turner, Matthew A. P.; Brunissen, Fanny; Stavros, Vasilios G.; Garnier, Gil; Allais, Florent; Saito, Kei
Abstract : Through structure–activity relationship study and density functional theory, this research designs novel lignin-based photo-responsive crosslinkable polymer with engineerable self-healing properties by utilizing a green photo-polymerization method. Abstract : Lignocellulose-derived p -hydroxycinnamic acids possess the photo-responsive reversible α, β-unsaturated ester moiety, a reactive structural feature that functions as the basis of the photo-reversible [2 + 2] cycloaddition reaction. To explore the potential of these naturally occurring compounds in the field of self-healing materials, novel bio-based photo-crosslinkable lignin- and glycerol-derived polyfunctional monomers having cinnamate groups were produced using a sustainable process from vanillin and syringaldehyde, two compounds readily obtained from the oxidation of lignin. Through a Structure–Activity Relationship (SAR) study, the structural design of these bio-based monomers was optimized with regards to the crosslinking/decrosslinking extent and the self-healing capacity of the corresponding polymer material. The lignin- and glycerol-derived tri-functional monomer with 4- O -propyl-ferulate moieties has facilitated the design of a new family of bio-based, environment-friendly and reversible self-healing materials for widespread applications. Computational density-functional theory (DFT) and time-dependent DFT calculations were further used for the verification of the SAR study in terms of dimerization energy of the synthesized monomers.